Decrements in neuromuscular performance and increases in creatine kinase impact training outputs in elite soccer players - Malone, S.; Mendes, B.; Hughes, B.; Roe, M.; Devenney, S.; Collins, K.; Owen, A. (The Journal of Strength and Conditioning Research, 2018)
The aim of the current investigation was to understand the impact of pretraining neuromuscular performance and creatine kinase (CK) status on subsequent training performance in elite soccer players. Thirty soccer players (age: 25.3 ± 3.1 years; height: 183 ± 7 cm; mass: 72 ± 7 kg) were involved in this observational study. Each morning before training, players completed assessments for neuromuscular performance (countermovement jump; CMJ) and CK levels. Global positioning technology provided external load: total distance, high-speed distance, sprint distance, accelerations, decelerations, average metabolic power, explosive distance, and high metabolic power distance (>25.5 W/kg). Mixed-effect linear models revealed significant effects for CK and CMJ Z-score on total high-speed distance, very high-speed distance, accelerations, decelerations, explosive distance, and maximal velocity. Effects are reported with 90% confidence limits. A CK Z-score of +1 corresponded to a -5.5 ± 1.1, -3.9 ± 0.5, -4.3 ± 2.9%, -4.1 ± 2.9%, -3.1 ± 2.9%, and -4.6 ± 1.9%, reduction in total high-speed distance, very high-speed distance, accelerations, decelerations, explosive distance, and maximal velocity, respectively. Countermovement jump Z-score of -1 corresponded to a -3.5 ± 1.1, -2.9 ± 0.5, -2.1 ± 1.4, -5.3 ± 2.9%, -3.8 ± 2.9%, -1.1 ± 2.9%, and -5.6 ± 1.2% reduction in these external load measures. Magnitude-based analysis revealed that the practical size of the effect of a pretraining CMJ Z-score of -1 and CK Z-score of +1 would have on total high-speed distance, very high-speed distance, high metabolic power distance (>25.5 W/kg), accelerations, decelerations, explosive distance, and maximal velocity was likely negative. The results of this study suggest that systematic pretraining monitoring of neuromuscular and muscle stress within soccer cohorts can provide coaches with information about the training output that can be expected from individual players during a training session.